Shadow and shelter : the swamp in southern culture - Wilson, Anthony, 1975- (University Press of Mississippi, 2006)
To early European colonists the swamp was a place linked with sin and impurity; to the plantation elite, it was a practical obstacle to agricultural development. For the many excluded from the white southern aristocracy--African Americans, Native Americans, Acadians, and poor, rural whites--the swamp meant something very different, providing shelter and sustenance and offering separation and protection from the dominant plantation culture. Shadow and Shelter: The Swamp in Southern Culture explores the interplay of contradictory but equally pre-vailing metaphors: first, the swamp as the undersi.